2017
DOI: 10.1080/02770903.2016.1247169
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma in Batumi, Georgia: Prevalence and environmental correlates

Abstract: The findings show a low prevalence of ever-diagnosed asthma in the examined population. Nosological tradition and similar correlates of asthma and spastic bronchitis suggest that some cases of asthma might be included in the diagnostic category of spastic bronchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…However, the prevalence of doctor‐diagnosed asthma reported in this study is within the range of those reported in the global pediatric asthma prevalence surveys on African children with reported proportions from 2.5% in Ethiopia and Burkina Faso to almost 10% in Swaziland . The prevalence of doctor‐diagnosed asthma from recent cross‐sectional studies from other low‐ and middle‐income countries were as high as 7.5% in Iran, 6% in India, 4.8% in China, 3% in Senegal, 2.5% in Mongolia, to 2% in Georgia …”
Section: Discussionsupporting
confidence: 71%
“…However, the prevalence of doctor‐diagnosed asthma reported in this study is within the range of those reported in the global pediatric asthma prevalence surveys on African children with reported proportions from 2.5% in Ethiopia and Burkina Faso to almost 10% in Swaziland . The prevalence of doctor‐diagnosed asthma from recent cross‐sectional studies from other low‐ and middle‐income countries were as high as 7.5% in Iran, 6% in India, 4.8% in China, 3% in Senegal, 2.5% in Mongolia, to 2% in Georgia …”
Section: Discussionsupporting
confidence: 71%
“…S 1 ). Further, we also performed meta-analyses for the family medical history of asthma in specific family groups separately, including paternal asthma (11 studies) [ 26 , 27 , 62 , 68 , 92 , 113 , 114 , 117 , 119 , 120 , 138 ], maternal asthma (15 studies) [ 26 , 27 , 62 , 68 , 73 , 84 , 89 , 92 , 113 , 117 , 119 , 120 , 123 , 134 , 138 ], parental asthma (9 studies) [ 26 , 66 , 72 , 78 , 88 , 93 , 118 , 121 , 122 ], and sibling’s asthma (4 studies) [ 26 , 65 , 123 , 138 ]. The combined risk estimates for asthma were also significantly increased in these four meta-analyses (pooled OR ranged between 3.22 and 4; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 76 studies have investigated housing-related factors and their association with asthma [ 16 18 , 25 , 26 , 38 , 52 , 53 , 58 60 , 67 , 72 , 73 , 79 , 82 , 85 , 88 , 91 , 94 , 95 , 97 , 98 , 105 , 111 , 118 120 , 125 , 127 , 129 , 130 , 135 , 136 , 138 , 142 182 ]. In these studies, frequently investigated housing-related risk factors of asthma included household dampness (18 studies) [ 17 , 67 , 72 , 82 , 85 , 88 , 125 , 130 , 142 , 143 , 146 , 147 , 150 , 157 , 166 , 171 , 174 , 180 ], traffic pollution (14 studies) [ 16 , 18 , 53 , 58 , 127 , 129 , 130 , 135 , 148 , 149 , 172 , 173 , 176 , 181 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations